2023
DOI: 10.3390/s23042130
|View full text |Cite
|
Sign up to set email alerts
|

Signal Quality Analysis for Long-Term ECG Monitoring Using a Health Patch in Cardiac Patients

Abstract: Cardiovascular diseases (CVD) represent a serious health problem worldwide, of which atrial fibrillation (AF) is one of the most common conditions. Early and timely diagnosis of CVD is essential for successful treatment. When implemented in the healthcare system this can ease the existing socio-economic burden on health institutions and government. Therefore, developing technologies and tools to diagnose CVD in a timely way and detect AF is an important research topic. ECG monitoring patches allowing ambulator… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
4
0
1

Year Published

2023
2023
2025
2025

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 14 publications
(5 citation statements)
references
References 43 publications
0
4
0
1
Order By: Relevance
“…However, the percentage of time with high signal quality in all collected data remained stable over time and was around 60%. Moreover, further analysis of signal quality showed no significant difference in the quality changes between the days [27]. Other research has shown that monitoring for up to 14 days is already feasible with the self-adhesive Zio Patch [18], but the influence of high-intensity activities was not addressed.…”
Section: Interpretation Of Findingsmentioning
confidence: 89%
See 2 more Smart Citations
“…However, the percentage of time with high signal quality in all collected data remained stable over time and was around 60%. Moreover, further analysis of signal quality showed no significant difference in the quality changes between the days [27]. Other research has shown that monitoring for up to 14 days is already feasible with the self-adhesive Zio Patch [18], but the influence of high-intensity activities was not addressed.…”
Section: Interpretation Of Findingsmentioning
confidence: 89%
“…Quality analysis was performed using Python (Python Software Foundation). The quality of the ECG recording from the patch during exercise was analyzed using a Signal Quality Indicator (SQI) which resulted in being the best performing one when comparing different SQI metrics with annotated quality levels [27]. This SQI is based on the comparison of successive QRS complexes.…”
Section: Signal Quality During Traditional Exercise Testingmentioning
confidence: 99%
See 1 more Smart Citation
“…За час досліджень цієї технології, що наразі тривають, з'явились роботи, що демонструють її певні діагностичні переваги. За даними I. Campero-Jurado і співавторів порівняно зі стандартним підходом, патч-монітори на 56,7 % більше ідентифікували прояви аритмії протягом тривалого періоду використання, що має принципове значення для прогнозування та профілактики серцевосудинних подій [7].…”
Section: оригінальні дослідженняunclassified
“…With adult ECG, a high-pass filter of 0.5 Hz is used in combination with a notch filter at the mains-electricity frequency (e.g., 50 Hz or 60 Hz). The 0.5 Hz threshold along with a notch filter is the default setting in the Neurokit2 open source Python (Python Software Foundation, Wilmington, DE, USA) library for ECG peak detection [ 116 ] and in other studies (e.g., [ 117 ]), while also being the same lower bound used for monitor-quality ECGs [ 118 ]. The Neurokit2 peak detection method (default settings) was used to detect R peaks on the preprocessed ECG signal [ 116 ], where the QRS complexes are identified based on the steepness of the absolute gradient of the ECG, and the local maxima are identified as the R waves.…”
Section: Softwarementioning
confidence: 99%